Development of Foreign Language Mastery Skills in the Process of Independent Study (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyzes the organization of independent study and students' thinking ability in the credit module system. The student's active life position is especially evident when comparing previously existing knowledge and concepts with newly acquired knowledge. Allows students to adjust any technology to suit the structure, functions, content goals and objectives of teaching in a particular group of students.